SYSTEM OF PHONEMES AND SYSTEM OF PHONEMIC OPPOSITIONS OF THE GOTHIC LANGUAGE - Park, S. (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article on the material of the text of the Gothic Bible (Codex Argenteus)treats the system of phonemes and the system of phonemic oppositions of the Gothic language on one synchronic state, in the middle of the first millennium AD. The possibilities of our study are limited since the East Germanic language evolution broke long before the time of the appearance of the first written texts in the West and North Germanic (Scandinavian) languages, which complicates reconstruction of the system of phonemes of the Gothic language in the period from the collapse of the common Germanic linguistic unity to the distinction of different developmental lines of language systems of the Old Germanic languages. Available linguistic literature shows the lack of a single integrated approach to phonetics and phonology of the Gothic language. In the article, the system of phonemes and the system of phonemic opposition are considered as the result of the interaction of functional, structural and anthropophonic factors of phonological evolution within the framework of the kinemic theory. The article examines different phonological processes and gives explanations of the sound changes in the history of the Gothic language. Phonemic oppositions are viewed as the main object of phonology in general and diachronic phonology in particular. The article corroborates the thesis about the system of phonemes and the system of phonemic oppositions of the Gothic language as the result of one dynamic process, all the stages of which are linked as causes and consequences of one another. _____________ References • Gamkrelidze T.V., Ivanov Vjach. Vs. Indojevropejskij jazyk i indojevropejtsy. Reconstruktsija i istoriko-tipologicheskij analiz prajazyka i protokultury. – T. I. – Tbilisi: Izdatelstvo Tbilisskogo universiteta, 1984.- 428 s. • Gukhman M.M. Gotskij jazyk. Moskva: Izdateljstvo literatury na inostrannykh jazykakh, 1958. – 288 s. • Zadorozhnyj B.M. Porivnjaljna fonetyka i morfolohija hotsjkoji movy. – Lviv: Vydavnytstvo Lvivskoho universytetu, 1960. – 297 s. • Plotkin V. Ja. Evoljutsija fonologicheskikh system. – Moskva: Nauka, 1982. – 128 s. • Plotkin V.Ja. Dinamika anglijskoj fonologicheskoj sistemy. – Novosibirsk: Zapadno-Sibirskoje knizhnoje izdatelstvo, 1967. – 169 s. • Sravnitelnaja grammatika germanskikh jazykov. – T. II. – Moskva: Nauka, 1962. – 402 s. • Bennett W.H. An Introduction to the Gothic Language. – New York: Modern Language Association, 1980. – 190 p. • Braune W. Gotische Grammatik. 19. Auflage.- Tübingen: Max Niemeyer Verlag, 1981. – 205 S. • Jellinek M.H. Geschichte der gotischen Sprache. – Berlin und Leipzig: Walter de Gruyter & Co., 1926. – 209 S. • Lambdin Th. O. An Introduction to the Gothic Language. – Eugene, Oregon: Wipf & Stock Publishers, 2006. – 361 p. • Mossé F. Manuel de la langue gotique: grammaire, textes, glossaire. – Paris: Aubier, 1942. – 272 p. • Plotkin V. The Evolution of Germanic Phonological Systems: Proto-Germanic, Gothic, West Germanic and Scandinavian. – Lewiston, New York, USA, Queenston, Ontario, Canada, Lampeter, Ceredigion, Wales, United Kingdom: The Edwin Mellen Press, 2008. – 230 p. • Rauch I. The Gothic Language: grammar, genetic provenance and typology, readings. – New York: Peter Lang Publishing, Inc., 2003. – 192 p. • Tollenaere F.de, Jones R. Word-Indices and Word-Lists to the Gothic Bible and Minor Fragments. – Leiden: E.J.Brill, 1976. – 583 p. • Voyles J.B. Early Germanic Grammar: Pre-, Proto-, and Post-Germanic Languages. – San Diego, California: Academic Press, Inc., 1992. – 302 p. • Wright J. Grammar of the Gothic Language. 2nd – Oxford: Clarendon Press, 1997. – 366 p.